2004
DOI: 10.1080/0265673031000150867
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ultrasound phased array design for tissue ablation for treatment of benign prostatic hyperplasia

Abstract: This paper describes the design, construction and evaluation of a two-dimensional ultrasound phased array to be used in the treatment of benign prostatic hyperplasia. With two-dimensional phased arrays, the focal point position can be controlled by changing the electrical power and phase to the individual elements for focusing and electronically steering in a three-dimensional volume. The array was designed with a steering angle of +/-14 degrees in both transverse and longitudinal directions. A piezoelectric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…This choice of element dimensions means that Grating lobes will be generated at unwanted locations. It has been found that a value of Grating lobe that is 20% of the maximum intensity is acceptable as it will not lead to temperatures above 41°C at the location of the Grating lobes, unless excessive acoustical power is used [8][9][10].…”
Section: Grating Lobesmentioning
confidence: 98%
See 1 more Smart Citation
“…This choice of element dimensions means that Grating lobes will be generated at unwanted locations. It has been found that a value of Grating lobe that is 20% of the maximum intensity is acceptable as it will not lead to temperatures above 41°C at the location of the Grating lobes, unless excessive acoustical power is used [8][9][10].…”
Section: Grating Lobesmentioning
confidence: 98%
“…Planar arrays are easier to dice, easier to acoustically match, and easier to electrically match. Previous effective flat arrays that were able to generate lesions in parts of the prostate include a two-dimensional (2-D) 8 9 8 phased array that was capable of electrically focusing and steering the ultrasound beam over a portion (less than half) of the prostate [8]. Another example is a 1.75-dimensional (1.75-D) 21 9 3 phased array that had the capability of focusing and steering the ultrasound beam at three different parallel planes inside the prostate [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a single channel power amplifier is needed to drive the single element transducer; however, multiple channels are needed for a 2D phased array. Although a 2D phased array can be electrically steered without the need to mechanically moving the array, the total steering angle is limited due to the formation of large grating lobes as the steering angle increases [9,13,14].…”
Section: Transducer Designmentioning
confidence: 99%
“…Improvements over 1-D arrays for the treatment of localized prostatic cancer can be achieved. Many multi-dimensional ultrasound phased arrays have been designed and built for the treatment of prostate diseases; that includes a 1.5-dimensional (1.5-D) phased array [10] (a 1.5-D array consists of three individual linear array that can be driven individually or connected together to form a single linear array), a 1.75-dimensional (1.75-D) phased array [11] (a 1.75-D array consists of many individual linear arrays that are driven separately), and a two-dimensional (2-D) phased array [12]. The advantage with a multi-dimensional phased array is that it has the capability of focusing and steering in a 3-dimensional (3-D) representation of the prostate without the need to physically move the array.…”
Section: Introductionmentioning
confidence: 99%